PENGARUH MOTIVASI, PEMANFAATAN TEKNOLOGI INFORMASI, SANKSI ADMINISTRASI, TINGKAT PENDAPATAN DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT KUDUS - Aida Nurul Husnina; Zaenal Afifi; Ulva Rizky Mulyani (Journal Accounting International Mount Hope, 2024)
The purpose of this study is to test and analyze the effect of motivation, utilization of information technology, administrative sanctions, income level and quality of tax services on motor vehicle taxpayer compliance. The primary data used in this study came from questionnaires distributed directly to respondents. The research subjects or population in this study were taxpayers whose motorized vehicles were registered at the Kudus Samsat Office. The sampling technique in this study used the Accidental Sampling technique with a sample size of 415 samples obtained based on the results of the Slovin formula calculation. The research method uses multiple linear regression analysis methods with SPSS version 26 software tools. The results of this study indicate that motivation and utilization of information technology have no effect on motor vehicle taxpayer compliance. Meanwhile, administrative sanctions, income levels and the quality of tax services have a positive effect on motor vehicle taxpayer compliance.